Drug treatment strategies for secondary lymphedema - Fu Yongda; Duan Man; Pu Luya; Du Jianshi (Guoji laonian yixue zazhi)
Secondary lymphedema is a chronic disease caused by lymphatic system dysfunction, which affects about 140 to 250 million people worldwide and has the second highest incidence among disabling diseases. With the advancement of malignant tumor treatment technology and the acceleration of the aging process of the population, the incidence of the disease continues to rise. Elderly patients present particular clinical challenges due to age-related lymphatic degeneration, diminished tissue regeneration, and frequent comorbidities. Current therapeutic strategies encompass surgical interventions, complex decongestive therapy, and pharmacotherapy with surgical options offering limited symptomatic relief despite their invasive nature, while complex decongestive therapy proves challenging for elderly patients due to its prolonged duration and modest efficacy. Pharmacotherapy has emerged as a particularly advantageous approach for geriatric populations, combining convenience with favorable safety profiles. Recent breakthroughs in understanding disease mechanisms have identified novel drug candidates that promote lymphatic regeneration through multiple pathways: targeting inflammatory responses, modulating immune microenvironments, stimulating lymphangiogenesis, and inhibiting fibrosis. These multimodal agents offer both symptomatic relief and pathological improvement, presenting new opportunities for developing personalized treatment regimens that balance efficacy and safety for elderly patients. This review systematically evaluates promising pharmacological agents and their mechanisms, with special emphasis on addressing the unique therapeutic needs of aging populations, aiming to advance treatment strategies from symptom control to causative therapy.